Domestic cattle (Bos taurus taurus) are motivated to obtain forage and demonstrate contrafreeloading - Van Os, Jennifer M. C. (PLoS One, 2018)
Domestic cattle (Bos taurus taurus) are adapted to digest high-roughage diets, but in confinement they are commonly fed low-roughage, high-energy diets. This practice may leave cattle with an unfulfilled need to consume forage. A way to quantify motivation is to require animals to work to access a resource. Using this method, we evaluated cattle motivation to obtain forage when fed high- or low-roughage diets during and 30 d before the study. Individual heifers were fed Sudan grass (Sorghum × drummondii) hay (high roughage, n = 6) or a diet with 12% forage (as fed, low roughage, n = 6) in an open feed trough. In a second trough, 200 g/d of Sudan grass hay were fed behind a push gate, to which additional weight was added daily until heifers no longer pushed. We predicted heifers would push heavier weights, show a shorter latency, and spend more time pushing the gate when fed a low- vs. high-roughage diet. Indeed, heifers fed a low-roughage diet pushed the gate immediately after hay delivery (1.7 min) and much sooner than those fed a high-roughage diet (75.7 min). On the day before they no longer pushed the gate, latency for heifers in the low-roughage treatment remained only 3.2 min after hay delivery. The suddenness with which they ceased pushing the next day suggests they were unable to move heavier weights to express their motivation. This may explain why maximum weight pushed and time spent pushing the gate did not differ between treatments. The gate pushing by heifers with unrestricted hay access is the first demonstration by cattle of contrafreeloading: performing work to obtain a resource that is simultaneously available for free. In conclusion, consuming forage is important to cattle and is affected by both their primary diet and an internal motivation to work to obtain feed.